Oil Price Shock and Structural Changes in CMEA Trade. Pouring Oil on Troubled Waters? - Elisabeth Beckmann; Jarko Fidrmuc (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2009)
We analyse trade between countries of the Council of Mutual Economic Assistance in Eastern Europe between 1950 and 1990. Despite central planning and political motivation of the CMEA, we show that trade could be explained by standard demand factors surprisingly well. Moreover, we document that the oil price crisis had several repercussions on Eastern Europe. The Soviet Union as a supplier of crude oil benefited from the energy crisis in the 1970s. In particular, it used energy exports as an instrument of foreign policy. In turn, the responses of the individual CMEA countries in Central Europe were largely different.
urn:nbn:de:bvb:19-epub-10963-7
Keywords: F14; C22; N74; 330; economic history; free trade areas; political economy; structural break; gravity model; oil price; CMEA trade; Internationale Wirtschaftsbeziehungen; Gravitationsmodell; Handelsgeschichte; Ölpreis; Außenpolitik; Sowjetisch; Neue politische Ökonomie; RGW-Staaten; Osteuropa